Anxiety, Depression, Disease Disability, and Health-Related Quality of Life in Rheumatoid Arthritis Patients during the Coronavirus Disease 2019 Pandemic: A Cross-Sectional Study - Shiekha S Alaujan; Haya M Almalag; Shahad M Alshehri; Jumanah M Alkendi; Mohamad A Almansour; Layla N Alanizy; Mohammed Omair (Journal of Nature and Science of Medicine, 2022)
Purpose: The coronavirus disease 2019 (COVID-19) pandemic has posed a threat to global health, including mental health. This study aimed to examine the impact of the pandemic on psychological health and to identify the factors associated with anxiety in patients with rheumatoid arthritis (RA) in Saudi Arabia. Materials and Methods: A cross-sectional observational study was conducted between September and November 2020, at the rheumatology clinics of two tertiary care hospitals. Eligible participants were adults with a confirmed diagnosis of RA. Data collected included socio-demographics, contact history, commitment to COVID-19 precautionary measures, medication-taking behavior, the hospital anxiety and depression scale (HADS), the European Quality of Life (QoL) measure (EQ-5D-3L), and the health assessment questionnaire disability index (HAQ-DI). Results: Of the 252 invited eligible patients, 204 agreed to participate. The majority were aged 41–50 years (28.2%), female (86.5%), and nonsmokers (96%), had at least one comorbidity (38.8%), had missed medications (8.8%), and had psychiatric illnesses or were on psychiatric medication for the past 3 months (15.4%). Borderline-abnormal anxiety levels were reported in 32.8% of patients. The mean standard deviation score for HADS depression was 3 (3), that for the EQ-5D-3L index was 0.587 (0.378), and that for the HAQ-DI was 0.947 (0.887). After adjusting for age, sex, presence of psychiatric illnesses or psychiatric medication use and noncompliance with medication, higher levels of anxiety were significantly associated with a higher level of depression, RA disability index, and pain intensity (p-value< 0.05). In contrast, higher health-related QoL was significantly associated with lower levels of anxiety (p-value< 0.001). Conclusion: During the mid-phase of the pandemic in Saudi Arabia, almost one-third of RA patients reported the presence of anxiety symptoms. Higher anxiety levels were found to be associated with depression, health-related QoL, and disease disability in RA patients.